Studies on Blood Coagulation and Fibrinolysis in Patients Bitten by Bothrops jararaca (jararaca) - Maruyama, M; Kamiguti, Aura S; Cardoso, J L C; Sano-Martins, Ida S; Chudzinski, Ana M; Santoro, M L; Morena, P; Tomy, Sandra C; Antonia, Luci C; Mihara, H; Kelen, Eva M A (Thrombosis and Haemostasis, 1990)
The blood coagulation and the fibrinolytic systems of nine patients envenomed by Bothrops jararaca in São Paulo (Brazil) were studied. Five of the accidents were caused by young snakes (<50 cm). On admission, four patients had non-clotting and three partially-clotting blood. Fibrinogen levels were decreased due to the thrombin-like activity of the venom as expected. Consequent secondary activation of the fibrinolytic system was evident from the low levels of alpha-2-antiplasmin and the high titres of fibrin(ogen) degradation products. High titres of cross-linked fibrin fragment D (D-dimer) in seven patients together with decreased platelet counts and/or factor V, and/or factor VIII in some, suggests intrinsic thrombin formation as these factors are not consumed in the defibrinogenation induced by venom thrombin-like fractions such as Ancrod and Batroxobin. However, normal or increased levels of antithrombin III in all and normal levels of factor II in eight patients do not support this interpretation. The existence of variable concentrations of other proteins in the venom of B. jararaca such as botrocetin and thrombocytin isolated from B. jararaca and B. atrox or crotalocytin from Crotaliis horridus venom should be considered. Such proteins are known to activate factors V, VIII, XIII, and platelets without affecting prothrombin (factor II) and antithrombin III. Slower recovery of the haemostatic disturbances after antivenom administration to patients bitten by young snakes suggests a more severe coagulopathy in such accidents. This is supported by clinical observations.